All-sky search for time-integrated neutrino emission from astrophysical sources with 7 yr of IceCube data - Aartsen, MG; Abraham, K; Ackermann, M; Sarkar, S; IceCube Collaboration (Institute of Physics, 2017)
Since the recent detection of an astrophysical flux of high-energy neutrinos, the question of its origin has not yet fully been answered. Much of what is known about this flux comes from a small event sample of high neutrino purity, good energy resolution, but large angular uncertainties. In searches for point-like sources, on the other hand, the best performance is given by using large statistics and good angular reconstructions. Track-like muon events produced in neutrino interactions satisfy these requirements. We present here the results of searches for point-like sources with neutrinos using data acquired by the IceCube detector over 7 yr from 2008 to 2015. The discovery potential of the analysis in the northern sky is now significantly below E 2 v doφ/dE v = 10 -12 TeV cm -2 s -1 , on average 38% lower than the sensitivity of the previously published analysis of 4 yr exposure. No significant clustering of neutrinos above background expectation was observed, and implications for prominent neutrino source candidates are discussed.